Multi-stage identification scheme for detecting damage in structures under ambient excitations - Bao, C.; Hao, Hong; Li, Z. (Institute of Physics Publishing, 2013)
Structural damage identification methods are critical to the successful application of structural health monitoring (SHM) systems to civil engineering structures. The dynamic response of civil engineering structures is usually characterized by high nonlinearity and non-stationarity. Accordingly, an improved Hilbert-Huang transform (HHT) method which is adaptive, output-only and applicable to system identification of in-service structures under ambient excitations is developed in this study. Based on this method, a multi-stage damage detection scheme including the detection of damage occurrence, damage existence, damage location and the estimation of damage severity is developed. In this scheme, the improved HHT method is used to analyse the structural acceleration response, the obtained instantaneous frequency detects the instant of damage occurrence, the instantaneous phase is sensitive to minor damage and provides reliable damage indication, and the damage indicator developed based on statistical analysis of the Hilbert marginal spectrum detects damage locations. Finally, the response sampled at the detected damage location is continuously analysed to estimate the damage severity. Numerical and experimental studies of frame structures under ambient excitations are performed. The results demonstrate that this scheme accomplishes the above damage detection functions within one flow. It is robust, time efficient, simply implemented and applicable to the real-time SHM of in-service structures.